2006
DOI: 10.1080/13603120600797831
|View full text |Cite
|
Sign up to set email alerts
|

School leadership in context: Narratives of practice and possibility

Abstract: In this paper, we critique the study of school leadership for its normative, singular, and evolutionary tendencies. Through an empirical study of leadership we offer an approach that suggests new possibilities for the field. Through the use of a qualitative, grounded theory methodology, we developed profiles of principals that illustrate a variety of different leadership types. We describe the types of leadership that teachers and principals negotiated in the contexts of reform and principal succession. Our ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Her descriptions of the support she gave colleagues and the comments of the recipients of that support made evident to us the importance of interaction between classroom teachers during any initiative focused on raising student achievement school‐wide and changing teachers' beliefs about how that information can raise achievement. This aligned with the literature which suggests that using assessment tools to measure student achievement needs rarely changes student achievement outcomes unless teachers collectively believe they have the potential to have a positive impact on student achievement (see, e.g., Goddard et al, ; Timperley et al, ).…”
Section: Findings and Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Her descriptions of the support she gave colleagues and the comments of the recipients of that support made evident to us the importance of interaction between classroom teachers during any initiative focused on raising student achievement school‐wide and changing teachers' beliefs about how that information can raise achievement. This aligned with the literature which suggests that using assessment tools to measure student achievement needs rarely changes student achievement outcomes unless teachers collectively believe they have the potential to have a positive impact on student achievement (see, e.g., Goddard et al, ; Timperley et al, ).…”
Section: Findings and Discussionsupporting
confidence: 73%
“…As Bronfenbrenner (1979Bronfenbrenner ( , 2005 highlights, providing a school environment where there is effective classroom management involves school leaders working closely with all staff in the school and developing connected networks with parents. Cole (1996) and Henze and Arriaza (2006), who consider student learning from a sociocultural perspective, point out that because school leaders are not separate identities but are embedded within wider social and cultural contexts, the political realities of society impact on their decision-making and implementation of educational policy and programmes within the school environment (Gordon & Patterson, 2006;Strike, 1999). Shields and Sayani (2005) propose that effective principals cater for students and teachers within the school environment in a way that gives them confidence that the school is a safe space within which to teach and learn, where each person is respected and valued, and where each has a feeling of belonging (see also Day, 2005;Moos, Krejsler & Kofod, 2008).…”
Section: Literacy Learning and Developmentmentioning
confidence: 99%
“…Supporting these results, the study conducted by Hebert (2003) reveals that these two factors affect job satisfaction positively. Also, it was found that teachers expected principals to be trustable (Oplatka, 2004), effective school principals were ones who cared about and recognized others (Gordon and Patterson, 2006), respected individuals and showed understanding (Knoop, 1994;Oplatka, 2004). School principals' leader ship showing consideration of Cerit: The Effects of Servant Leadership Behaviours of School Principals .…”
Section: Discussionmentioning
confidence: 98%
“…Instrument. As society and schools have changed, so have the responsibilities and leadership expectations of educational leaders (Gordon & Patterson, 2006;Marshall, 1993;Marzano, et al, 2005). An abundance of national and state initiatives that address effective leadership have attempted to create contemporary standards for school administrators (Gordon & Patterson, 2006;Reeves, 2004).…”
Section: North Carolina Standards For School Executive and The Princimentioning
confidence: 99%
“…As society and schools have changed, so have the responsibilities and leadership expectations of educational leaders (Gordon & Patterson, 2006;Marshall, 1993;Marzano, et al, 2005). An abundance of national and state initiatives that address effective leadership have attempted to create contemporary standards for school administrators (Gordon & Patterson, 2006;Reeves, 2004). Recognizing that the success of schools is heavily influenced by the quality of the principal, North Carolina revised its standards for school leaders in order to increase academic achievement and prepare students for a prosperous life (North Carolina State Board of Education, 2008).…”
Section: North Carolina Standards For School Executive and The Princimentioning
confidence: 99%